Hubungan Kepatuhan Minum Obat Dengan Kontrol Tekanan Darah Pada Pasien Hipertensi - Elvira Savidni; Suaib Suaib (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Hypertension is a non-communicable disease that is a public health problem due to its increasing prevalence and the risk of serious complications. One important factor in controlling blood pressure in hypertensive patients is adherence to antihypertensive medication. However, patient adherence to medication is still relatively low. This study aims to determine the relationship between medication adherence and blood pressure control in hypertensive patients. This study used a quantitative method with an analytical design and a cross-sectional approach. The study sample was hypertensive patients undergoing treatment at health care facility X. Data were collected using a medication adherence questionnaire and blood pressure measurements, then analyzed using the Chi-Square test. The results showed a significant relationship between medication adherence and blood pressure control (p < 0.05). The conclusion of this study is that hypertensive patients who adhere to medication have a greater chance of achieving good blood pressure control.